Drawing Humanitarian Communication as Performativity: Visual Design of the Tigray Refugee Situation on the UN Refugee Agency UK Website - Piga, Antonio (Advances in Social Sciences Research Journal, 2023)
This article outlines the discursive construction of the refugee situation in Ethiopia’s Tigray region by examining photographs found on the United Nations Refugee Agency (UNHRC) United Kingdom website. The purpose is to discern humanitarian aid communication discourse not simply for its informational value, but also in its performative force of narrative to frame the refugee crisis as one that merits support (Chouliaraky 2017). Multimodal CDA and social semiotics (Kress and van Leeuwen 1999; Kress and van Leeuwen 2017) were employed in order to break down visual communication into elements, and to systematically reveal the performative practice of meaning in relation to the categories of settings, the represented participants, actions, angles, and proxemics. Both qualitative and quantitative analyses were conducted in order to determine the number of photos with a given feature. By highlighting the plight of those forcibly displaced and emphasising their uniqueness and personal experiences - in contrast to the dehumanised massified representation found in western media (Chouliaraky 2017; Adi and Cheregi 2015) -, the phenomenon of their forced fleeing from Tigray is humanised. In line with Bellander (2021), the UNHRC is constructed as being trustworthy and actionable, and refugees are clearly depicted as being in urgent need of support. Visitors to the UK website are invited to feel they are involved with the life of the refugees and morally engaged in “the work performed by the organization” (Bellander 2021: 310). By means of the combination of specific affection drawing on discourses of morality, solidarity and ethical equality, the overall images provide “the symbolic conditions under which we are invited to imagine the predicament of these sufferers” (Chouliaraky 2017: 5) and in so doing to appeal to a force that will work towards a practical push towards action.